2015
DOI: 10.1038/ejhg.2015.260
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of the spectrum of ITGB6-related disorders to adolescent alopecia, dentogingival abnormalities and intellectual disability

Abstract: Alopecia with mental retardation (APMR) is a very rare disorder. In this study, we report on a consanguineous Pakistani family (AP91) with mild-to-moderate intellectual disability, adolescent alopecia and dentogingival abnormalities. Using homozygosity mapping, linkage analysis and exome sequencing, we identified a novel rare missense variant c.898G4A (p.(Glu300Lys)) in ITGB6, which co-segregates with the phenotype within the family and is predicted to be deleterious. Structural modeling shows that Glu300 lies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Patients with mutations in ITGB6 have since been reported (MIM #616221) with either hypomineralized pitted enamel, similar to that reported in the Itgb6 null mouse (Poulter et al, 2014a ), or hypoplastic enamel with a rough surface (Wang et al, 2014b ), both recessively inherited. More recently, Ansar et al ( 2015 ) reported a consanguineous family with a homozygous ITGB6 mutation with adolescent alopecia, intellectual disability and dentogingival abnormalities with rough, discolored enamel. However, it is unclear if these additional phenotypes result from the ITGB6 variant or are co-segregating, for example, due to an undetected copy number variant.…”
Section: The Genetics Of Amelogenesis Imperfectamentioning
confidence: 99%
“…Patients with mutations in ITGB6 have since been reported (MIM #616221) with either hypomineralized pitted enamel, similar to that reported in the Itgb6 null mouse (Poulter et al, 2014a ), or hypoplastic enamel with a rough surface (Wang et al, 2014b ), both recessively inherited. More recently, Ansar et al ( 2015 ) reported a consanguineous family with a homozygous ITGB6 mutation with adolescent alopecia, intellectual disability and dentogingival abnormalities with rough, discolored enamel. However, it is unclear if these additional phenotypes result from the ITGB6 variant or are co-segregating, for example, due to an undetected copy number variant.…”
Section: The Genetics Of Amelogenesis Imperfectamentioning
confidence: 99%
“…In healthy periodontal tissues, both αvβ6 integrin and TGF-β1 are constitutively expressed in the JE 25 , and it is likely that αvβ6 integrin-mediated activation of TGF-β1 is involved in the regulation of the anti-inflammatory response in these tissues. In periodontal disease, the expression of αvβ6 integrin becomes strongly downregulated in the PE, and patients with mutations in the β6 integrin gene can develop severe periodontal disease 25 , 27 . In addition, mice deficient in β6 integrin spontaneously develop periodontal disease that involves PE formation, inflammation and bone loss 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Two cases are illustrative of common themes in medical genomics (Prada et al, 2014;Ansar, 2015;Taylan et al 2016). A non-sense mutation in GRIK2 caused a more complex phenotype than it was previously recognized for this gene.…”
Section: Discussionmentioning
confidence: 99%